1999
DOI: 10.1007/s001340050818
|View full text |Cite
|
Sign up to set email alerts
|

Does bronchial thermodilution allow estimation of cardiac output?

Abstract: We conclude that the Stewart-Hamilton equation may be extended to bronchial temperature-time curves for estimations of cardiac output. At this time, however, we do not advocate bronchial thermistors as suitable and less invasive alternatives to pulmonary arterial catheters for routine cardiac output measurements in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The limitation of this technique may be the undetected heat exchange during the passage through the pulmonary vasculature. The CI and SVI may consequently be overestimated, but it has been reported previously, that the heat exchange in the lungs is negligible (Arfors et al 1971;Bock et al 1988;Loer et al 1999). In addition, this potential error was reproduced systematically in all of our experiments so that a valid comparison could be made between the positions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The limitation of this technique may be the undetected heat exchange during the passage through the pulmonary vasculature. The CI and SVI may consequently be overestimated, but it has been reported previously, that the heat exchange in the lungs is negligible (Arfors et al 1971;Bock et al 1988;Loer et al 1999). In addition, this potential error was reproduced systematically in all of our experiments so that a valid comparison could be made between the positions.…”
Section: Discussionmentioning
confidence: 97%
“…Briefly, a bolus of 0.1 ml ice cold 0.9% saline was injected into the right atrium through the jugular vein catheter. CI was calculated using the following formula: where T rat represents the rat body temperature, T inject is the injectate temperature (4°C), BW is the body weight, V inject is the injectate volume (0.1 ml), V dead is the dead space volume of the venous catheter (0.02 ml), is the integral of temperature variation during an interval of 14 s, and k spec is the density factor defined as the product of specific heat and specific gravity of saline divided by the same product for blood ( k spec = 1.102 for 0.9% saline) (Loer et al 1999). We did not make any correction for the potential heat exchange during the transit through the lung as it was previously shown that this loss of thermal energy through the lung tissue is negligible and that the total amount of the injectate is retrieved in the systemic side after one passage though the pulmonary vasculature (Arfors et al 1971; Bock et al 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Loer and co-workers show that flow calculations obtained from bronchial temperaturetime curves correlate with those from the aorta [21], and Neumann has developed a technique that may allow estimation of extravascular lung water and intrathoracic blood volume by single thermodilution technique [22]. Interestingly, further new applications of this principle are illustrated in the present issue of Intensive Care Medicine.…”
mentioning
confidence: 94%